Proposed Supply Chain Strategy for Metal Craft Home Industries (The Indonesian Journal of Business Administration, 2015)
Abstract - Usaha Logam Kudus is a home industry association which consists of 4 Koperasi Unit Bersama. The cluster location is at Kecamatan Mejobo. This  home industries  has become  the center of metal  production, which  will be developed as the one of Kudus income sources and man power absorption. As the globalization, the competition among industries is increasing. For Usaha Logam Kudus, the blacksmiths are facing the problem with the decrease of the selling  revenue, in which it has direct impact to the existence of the business itself in the market  competition. As small-medium enterprise  which has limited capacity and capability, the operation of the cluster need to be improved. Data collection method of interview, observation and document review were used in this project. The result of the analysis indicates the condition of Usaha Logam Kudus. The level of awareness regarding to supply chain is still low. The proposed operation strategy is conducted by redesign organization structure, supplier contracts, and network configurations. Moreover Usaha Logam Kudus should also be concerned about purchasing planning which is influenced by price fluctuation, limited sales marketing activities, entities collaboration, production and quality control, limited human resources, the supplier relationships, documentation Keyword: Operation Strategy, Supply Chain, Small Medium Enterprise